Single-Chip 20 GHz VCO and Frequency Divider in SiGe Technology - Ettinger, Klaus; Stelzer, Andreas; Diskus, Christian; Thomann, Wolfgang; Fenk, Josef; Weigel, Robert (IEEE MTT-S International Microwave Symposium Digest, 2002)
This paper presents the design, implementation and testing of a fully integrated 20 GHz voltage controlled oscillator, a frequency divider with a divide ratio of 16, as well as an output driver. All blocks are integrated on one IC with an area of 890 × 890 μm 2 and are fabricated in a production SiGe bipolar technology. The VCO is a varactor-tuned LC-type oscillator with a tuning range of 600 MHz. The differential signal of the output driver is converted to a single-ended signal by an external microstrip balun and delivers a maximum of 2 dBm of output power into a 50 Ω load. The chip works with a single supply voltage of 3.6 V, the VCO draws 12 mA of supply current, divider and output driver consume 17 mA and 51 mA, respectively. The measured phase-noise of the VCO is -85 dBc/Hz at 1 MHz offset frequency
elib2cris::1512001600,ettinger2002
Keywords: Bipolar integrated circuits; Frequency conversion